Efficacy of vitamin D supplementation in asthmatic children with vitamin D deficiency: A randomized controlled trial (ESDAC trial). Issue 3 (4th December 2020) - Jat, Kana Ram; Goel, Nancy; Gupta, Nandita; Gupta, Chandra Prakash; Datta, Sudip; Lodha, Rakesh; Kabra, Sushil K.
Abstract: Background: Vitamin D supplementations for asthma control had shown inconsistent results. We aimed to study efficacy and safety of vitamin D supplementation in asthmatic children who were vitamin D deficient. Methods: This double‐blind, randomized controlled trial enrolled asthmatic children of 4‐12 years of age who had 25‐hydroxyvitamin D [25(OH)D] levels <20 ng/mL. The participants were randomized to receive either vitamin D orally 1000 IU/d for 9 months or similar‐looking placebo. The primary outcomes were the proportion of children having the Childhood Asthma Control Test (CACT) score of ≥20 at the end of the treatment and adverse effects. Results: The trial included 250 children (125 in each group) with a mean age of 8.1 ± 2.3 years and 180 boys. The baseline parameters were similar between the groups, including CACT score (21.7 ± 4.2 vs 21.9 ± 3.6, vitamin D vs placebo). At the end of the study, the proportion of asthmatic children who had CACT score ≥ 20 was similar between vitamin D and placebo group (93.6% vs 92.0%, P  = .625). The number of exacerbations of asthma and side effect profile was also identical between the groups. 25(OH)D levels increased significantly in the vitamin D group (18.06 ± 7.11 vs 12.03 ± 5.98 ng/mL, P  < .001). The results did not change when we did subgroup analysis for children with baseline CACT score < 20 and 25(OH)D levels at the end of the study ≥20 ng/mL. Conclusion: Vitamin D supplementation in asthmatic children with vitamin D deficiency did not improve control of asthma. Abstract :